(3faMI GdQjMGfg hQTMI WdGA GdMGfIs - (3eMeO Cejf Hf aVd Gddg Hf eMH Gddg Hf eMeO GdeMHj GdMehj, eMH GdOjf , CHh HcQ,J (B1111 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeQ GdNaGLj GdeUQj,J (B1069 (3g` s
(3ChdgG (B:s
(3CfRg Gddg hCSHMg , hCSCdg GdJhajb hCSJefMg s
(3fSNI KGfjIs
(3hPjdg GdeDda HcJGH BNQ gh (B[(3Pjd GdfaMI hfjd GdefMI(B]s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B227s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B403 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B325 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs